2020
DOI: 10.3389/fgene.2020.00711
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Endurance Algorithm Prediction in the Field of Sports Performance

Abstract: Sport performance is influenced by several factors, including genetic susceptibility. In the past years, specific single nucleotide polymorphisms have been associated to sport performance; however, these effects should be considered in multivariable prediction systems since they are related to a polygenic inheritance. The aim of this study was to design a genetic endurance prediction score (GES) of endurance performance and analyze its association with anthropometric, nutritional and sport efficiency variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The study involved a group of cyclists with correct body weight, BMI and body fat. However, they did not show an association between polymorphismTrp64Arg and somatotype [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study involved a group of cyclists with correct body weight, BMI and body fat. However, they did not show an association between polymorphismTrp64Arg and somatotype [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis, along with psychological interventions, shows potential for personalised programming in university sports programmes (Hao et al, 2023;Herbert, 2022). Universities can use genomic research developments to do genetic testing to pinpoint genetic variants linked to endurance performance parameters, including VO2 max, lactate threshold, and muscle fibre composition (De la Iglesia et al, 2020). Equipped with this information, coaches and sports scientists can customise training protocols to maximise players' genetic advantages and target areas that may need work.…”
Section: Introductionmentioning
confidence: 99%
“…Adam Maszczyk and Artur Golas, on the other hand, used nonlinear regression models and neural network models in javelin throw, and the results showed that the neural network models had a higher prediction accuracy. The team led by Rocio de la Iglesia [3] biologically perspective to analyze the genetics of athletes and to identify genetically gifted athletes through the Genetic Hardening Predictive Score (GES) to improve shortcomings and improve athlete performance.…”
Section: Introductionmentioning
confidence: 99%